Reconstruction of extremely dense breast composition Utilizing inverse scattering technique integrated with Frequency-hopping approach - Ng, Shi Wei; Kismet, Hong Ping; Lim, Sin Yee; Wan Azlan, Bin Wan Zainal Abidin (Asian Research Publishing Network (ARPN), 2015)
The Forward-Backward Time-Stepping (FBTS) inverse scattering technique is utilized for breast composition reconstruction of an extremely dense breast model at different center frequencies. A numerical extremely dense breast phantom is used and resized to suit the Finite-Difference Time-Domain (FDTD) lattice environment utilizing twodimensional (2-D) FBTS technique. The average value of fibro glandular region for reconstruction with Frequencyhopping approach applied is much closer to average value of the actual image compared to the reconstruction without Frequency-approach applied. Hence, the composition of the extremely dense breast model can be reconstructed with Frequency-hopping approach is applied and the details of the reconstruction is also enhanced.